Diversity of freshwater fish at Sago Palm Wetlands, Nakhon Si Thammarat Province, Thailand (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suriya C, Satian C, Visut B, Supadha K. 2022. Diversity of freshwater fish at Sago Palm Wetlands, Nakhon Si Thammarat Province, Thailand. Biodiversitas 23: 6335-6344. Studies on the diversity of freshwater fish at Sago Palm Wetlands, Nakhon Si Thammarat Province, Thailand, were conducted in the period from March 2020 to November 2020. Fish samples were collected, encompassing the hot-dry season (March to June) and the rainy season (September to November) at 4 sampling zones, with 5 stations for each zone. Fish were caught using a seine net of 1 cm mesh size, 1.5m in length, and 1m in width. All data were analyzed to find out the fish diversity indices. The multivariate method was used to determine cluster analysis. A total of 3634 fish specimens, representing 62 species belonging to 24 families, were recorded during the sampling period. Cyprinidae was the major family, with Trichopsis vittatus containing the highest index of relative importance (IRI). The species diversity index of fish was in the range of 0.66 to 2.67; the evenness index was in the range of 0.64 to 0.95, and the species richness index ranged from 0.36 to 6.86, indicating an intermediate-low uniformity, with a medium species number in the area. The cluster analysis of the Bray-Curtis similarity index shows A division of the fish community into 2 clusters in the hot-dry season and 3 clusters in the rainy season, having a similarity percentage ranging between 42% and 95%, respectively. Also documented were one introduced species and one endangered fish species during sampling. The findings suggest that Sago Palm Wetlands is still inhabited by numerous fish species and should be conserved to ensure its aquatic animal richness for the future. This data provides information about the fish habitat in the Sago Palm Wetlands and can be used to update the checklists of fish species in the Tapi River, the Pak Phanang River, and the Trang River Basins. It also can be useful for the planning of fishing activities and the provision of guidelines for future research and conservation purposes.
Keywords: Cluster analysis, diversity pattern, fisheries resources, index of relative importance